Krakens and lies - Sutherland, Tui, 1978-; Sutherland, Kari H. (Sutherland, Tui, 1978- Menagerie., 2016)
When Logan and Zoe discover that someone is sabotaging the Menagerie at the same time that the basilisk escapes its enclosure and the merpeople go on strike, they must find a way to save all of the mythical creatures and their home.